The associations of nursing informatics competence and stress related to information systems (SRIS) in the well-being of nurses in Saudi Arabia 2024 - Muneera Marzouq Alenezi,; Fatemah Faleh Musleh ALMutiery,; Hind Turki Awdah Alanazi,; Lailah Salem AlEnazi,; Mona Fayad Funaitel Alanazi,; Maali Thamer Alenezi,; Mona Muteb Dakilallah Almutairi,; Amirah Bader Sanad Alanazi,; Ebtisam Faihan Almutairi,; Albandry Faihan Almutairi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The majority of nurses' working hours are spent using information systems. Increased usage of the systems is known to be a potential source of stress and necessitates that nurses possess sufficient nursing informatics competency.The workplace environment of nurses concerns nurse administrators and information technology; a well-established tool that assists healthcare and nurses in doing their job effectively. Nursing informatics competence and stress related to information systems can be important variables to understand the well-being of nurses using information systems. However, evidence is so far insufficient for understanding their associations and effects on the well-being of nurses. The study aims: To examine whether SRIS and nursing informatics competence are associated with stress and psychological distress in newly graduated nurses (NGNs) and experienced nurses. Methods: A cross-sectional study was conducted in KSA between January and March 2024. The participants were NGNs (n = 712) with less than two years of work experience and experienced nurses (n = 1226) with more than two years of work experience. The associations of nursing informatics and SRIS with nurses’ stress and psychological distress were analyzed with linear regression analysis. Analyses were conducted separately for NGNs and experienced nurses. Models were adjusted for age, gender, and work environment. Results: SRIS was associated with stress / psychological distress for both NGNs (β = 0.26 p < 0.001 / β = 0.22 p < 0.001) and experienced nurses (β = 0.21 p < 0.001/ β = 0.12 p < 0.001). Higher nursing informatics competence was associated with lower stress (β = 0.20 p < 0.001) and psychological distress (β = 0.16 p < 0.001) in NGNs, but not among experienced nurses. Conclusions: SRIS appears to be an equal source of stress and distress for nurses who are starting their careers and for more experienced nurses, who are also likely to be more experienced users of information systems. However, informatics competence played a more important role among NGNs and a lack of adequate competence seems to add to the strain that is already known to be high in the early stages of a career. It would be important for educational institutions to invest in nursing informatics so that new nurses entering the workforce have sufficient skills to work in increasingly digital health care.